Funções afim e quadrática: uma análise de avaliações externas para uma abordagem didática no ensino dessas funções - Távora Neto, Luiz Edson Pinheiro (2023)
The present work was developed with the intention of presenting considerations about the importance, for the teaching-learning process, of a didactic approach with the use of the GeoGebra Software and Problem Solving for the study of affine and quadratic functions. The methodology approached was a bibliographical research, based on data collected from external evaluations, which show that students have a deficit of knowledge in these mathematical subjects and that they need didactic approaches that aim to facilitate and implement the teaching-learning process in the study. of these functions. From this, an analysis of exhibitions and activities carried out in the classroom using the GeoGebra Software was used.